2018
DOI: 10.31047/1668.298x.v1.n35.20450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium and calcium upon the yield and fruit quality of Cucumis melo

Abstract: summaryThe aim of this work was to study the effect of potassium and calcium in combination with nitrogen upon the yield and fruit quality of outdoor-grown melon (Cucumis melo L.). Two experiments were simultaneously performed through the use of two cultivars: 'Honey Dew Green Flesh' (Inodorus group) and 'Sivan' (Charentais group). A completely randomized experimental design was used with nine treatments resulting in a factorial arrangement of 3 x 3 due to the use of three doses of K and three doses of Ca. Dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Rangel et al (2018) verified a linear increase in soluble solids in melon fruits with increased K concentration in the irrigation solution. When combining fertilization between K and calcium, Bouzo, Céccoli, and Muñoz (2018) also verified positive linear effect on soluble solids content with increase of these nutrients in the soil.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Rangel et al (2018) verified a linear increase in soluble solids in melon fruits with increased K concentration in the irrigation solution. When combining fertilization between K and calcium, Bouzo, Céccoli, and Muñoz (2018) also verified positive linear effect on soluble solids content with increase of these nutrients in the soil.…”
Section: Resultsmentioning
confidence: 66%
“…This increase in the concentration of sugars in the fruit may be associated with the role that K plays in apoplastic co-transport during the sucrose loading between the mesophyll and the phloem (WHITE; KARLEY, 2010). The literature is rich in approaches that confirm the positive effect of an increase of K on TSS in this crop, as found in Lin, Huang and Wang ( 2004), Demiral and Köseoglu (2005), Bouzo, Céccoli, and Muñoz (2018), Yang et al (2019) and Oliveira et al (2021). Thus, maintaining an adequate supply of K for melon plants ensures a better quality of the fruits, with regard to the degree Brix.…”
Section: Resultsmentioning
confidence: 69%
“…It can be assumed that the accumulation of melon metabolites is genetically determined but also strongly influenced by weather conditions. In addition, Bouzo et al [54] found different plant responses in two melon cultivars to potassium and calcium fertilization, suggesting that the chemical composition of melon fruit is also subject to environmental variability.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is responsible for proper plant cell division and for strengthening cell walls [40,41]. This nutrient has beneficial effects on fruit firmness and alleviating influence on physiological as well as pathogenic disorders in fruit [42][43][44]. Sulfur is essential to metabolism of amino acids [45] and interacts with N in protein synthesis and accumulation [46,47].…”
Section: Introductionmentioning
confidence: 99%